2017
DOI: 10.1002/pon.4387
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of patient activation in a community sample of breast and prostate cancer survivors

Abstract: Background Patient activation—the knowledge, skills and confidence to manage one’s health—is associated with improved self-management behaviors for several chronic conditions. This study assesses rates of patient activation in breast and prostate cancer survivors and explores the characteristics associated with patient activation. Methods A cross-sectional study of survivors with localized (Stage I or II) breast and prostate cancers who are post-treatment (between 1–10+ years) were recruited from four commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…Low activated patients had a greater number of comorbidities. Study in older adults 4 and cancer survivors 38 has shown comorbidity is an important factor in patient activation. These findings are somewhat expected given that managing multiple LTCs likely results in an inability to cope 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Low activated patients had a greater number of comorbidities. Study in older adults 4 and cancer survivors 38 has shown comorbidity is an important factor in patient activation. These findings are somewhat expected given that managing multiple LTCs likely results in an inability to cope 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with greater HA felt less satisfied with: a) the information they received [62] b) their care and the medical decisions they made [146,234], and c) were less confident they had received good treatment [137]. They also reported lower patient activation (i.e., the knowledge, skills, and confidence to manage one's health) [153] This suggests that the medical team may play an important role in the management of HA in this population.…”
Section: Plos Onementioning
confidence: 99%
“…Unfortunately, certain groups such as ethnic/racial minorities (National Center for Health Statistics, 2016), individuals with low income (United States Census Bureau, 2019b), and individuals with low educational attainment (Eneanya et al, 2016) have a higher proportion of disease burden compared to Whites, top income earners, and college graduates (Coylewright et al, 2014; O’Malley et al, 2018; Singh-Manoux et al, 2003). Indeed, there are a constellation of factors that determine health.…”
Section: Socio-economic Factors and Healthmentioning
confidence: 99%
“…Western Journal of Nursing Research 43(6) et al, 2016) have a higher proportion of disease burden compared to Whites, top income earners, and college graduates (Coylewright et al, 2014;O'Malley et al, 2018;Singh-Manoux et al, 2003). Indeed, there are a constellation of factors that determine health.…”
mentioning
confidence: 99%